PERANCANGAN SISTEM WAREHOUSE BANTUAN LOGISTIK KORBAN BENCANA ALAM, STUDI KASUS : GUNUNG MERAPI - Agus Purbayu; Yuliana Agustiningsih (Universitas Sebelas Maret, 2016)
Indonesia is situated at the confluence of the active tectonic plates, the mountains, and the climate is tropical, so make the most of its territory vulnerable to natural disasters. The number of disaster victims belong to very high compared to other countries. During this process of distribution logistical support from the Government is often less evenly, and the spread of the post often accumulate at some point, while there are still many victims don't get logistical support. Causes less equality the help of, among others, less equality the location information of the victim or the evacuation command post and causing material needs logistical support at each refugee command post. In the design of the system is carried out using several methods including needs analysis, system design, coding and testing. Data collection was done to perform needs analysis system of warehouse logistics assistance. Methods used in the collection of data is to conduct interviews and literature study. The design phase in the form of the design of the user interface of the software can be estimated before it made coding. The results in the form of a system of warehouse logistics assistance to natural disasters which can handle transaction processing, delivery and acceptance of the demand for goods. The Design of application include manage data items as well as members who are involved in it.